Educational Supervision: Models, Approaches, and Techniques in Enhancing Teacher Professionalism and Learning Quality - Angel Areysia Siagian; Fitri Sitorus; Sofia Wasti Gaberia Tambunan (International Journal of Educational Practice and Policy, 2025)
Improving the quality of education relies on teacher professionalism and the effectiveness of the learning process. Educational supervision plays a strategic role in this context, functioning not merely as administrative oversight but also as professional guidance to assist teachers in identifying strengths and weaknesses and planning for ongoing improvement. This article aims to examine and synthesize various models, approaches, and techniques of educational supervision that support the development of teacher competence and learning quality. The study uses a qualitative library research method, involving systematic selection and critical analysis of relevant academic books, peer-reviewed journal articles, and educational policy documents published in the last five years. The results of the review show that supervision models such as collaborative, clinical, educational-collaborative, digital-based, contemporary, and monitoring-evaluation-based supervision are effective in different contexts. These models are applied using directive, non-directive, and collaborative approaches, supported by both individual and group supervision techniques. A key insight from this study is that the success of educational supervision depends on its ability to adapt to teachers' needs and school contexts. Therefore, optimizing supervision practices through the integration of suitable models and flexible techniques can significantly enhance teacher professionalism and overall learning quality.